A STYLISTIC-SEMANTIC ANALYSIS OF DICTION IN IMAM SHAFI’I’S DA’IL AYYĀMA TAF’ALU MĀ TASYĀ’U AND ITS MORAL EDUCATIONAL VALUES - Tarisha Naila Sahrudin; Asep Sopian; Irfa Amalta (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study examines the stylistics of diction in Imam Shafi’is poem da’il ayyāma taf’alu mā tasyā’u (leave the days to do as they will) through a semantic stylistic perspective. While previous studies have widely explored its moral teachings, limited attention has been given to the role of diction at the semantic level in constructing moral meaning. This qualitative study employs content analysis through documentary study and literature review. The analysis applies Syihabuddin Qalyubi’s stylistic framework, particularly the semantic level (mustawā al-dalālī) focusing on lexical meaning (dalālah al-lafẓ al-mu'jamī) and its development through figurative stylistic elements at the imagistic level (mustawā al-taṣwīrī). The findings reveal that the lexical meaning develops into contextual meanings through stylistic devices such as methapor, personification, hyperbole, and imagery, generating semantic effects that reinforce moral values, including patience, humility, resilience, and trust in God (tawakkul). The study also identifies moral values across personal, social, and metaphysical dimensions, highlighting the integration of linguistic analysis and moral education. This study contributes to Arabic stylistics by demonstrating how semantic diction systematically constructs moral meaning in classical Arabic poetry.